Changes in malaria burden and transmission in sentinel sites after the roll-out of long-lasting insecticidal nets in Papua New Guinea. Issue 1 (December 2016) - Hetzel, Manuel; Reimer, Lisa; Gideon, Gibson; Koimbu, Gussy; Barnadas, Céline; Makita, Leo; Siba, Peter; Mueller, Ivo
Abstract Background Papua New Guinea exhibits a complex malaria epidemiology due to diversity in malaria parasites, mosquito vectors, human hosts, and their natural environment. Heterogeneities in transmission and burden of malaria at various scales are likely to affect the success of malaria control interventions, and vice-versa. This manuscript assesses changes in malaria prevalence, incidence and transmission in sentinel sites following the first national distribution of long-lasting insecticidal nets (LLINs). Methods Before and after the distribution of LLINs, data collection in six purposively selected sentinel sites included clinical surveillance in the local health facility, household surveys and entomological surveys. Not all activities were carried out in all sites. Mosquitoes were collected by human landing catches. Diagnosis of malaria infection in humans was done by rapid diagnostic test, light microscopy and PCR for species confirmation. Results Following the roll-out of LLINs, the average monthly malaria incidence rate dropped from 13/1, 000 population to 2/1, 000 (incidence rate ratio = 0.12; 95 % CI: 0.09–0.17;P < 0.001). The average population prevalence of malaria decreased from 15.7 % pre-LLIN to 4.8 % post-LLIN (adjusted odds ratio = 0.26; 95 % CI: 0.20–0.33;P < 0.001). In general, reductions in incidence and prevalence were more pronounced in infections withP. falciparum than withP. vivax . Additional morbidity indicators (anaemia, splenomegaly, self-reported fever) showed a decreasing trend in most sites. MeanAnopheles man biting rates decreased from 83 bites/person/night pre-LLIN to 31 post-LLIN (P = 0.008).Anopheles species composition differed between sites but everywhere diversity was lower post-LLIN. In two sites, post-LLINP. vivax infections in anophelines had decreased butP. falciparum infections had increased despite the opposite observation in humans. Conclusions LLIN distribution had distinct effects onP. falciparum andP. vivax . Higher resilience ofP. vivax may be attributed to relapses from hypnozoites and other biological characteristics favouring the transmission ofP. vivax. The effect on vector species composition varied by location which is likely to impact on the effectiveness of LLINs. In-depth and longer-term epidemiological and entomological investigations are required to understand when and where residual transmission occurs and whether observed changes are sustained.